Digestion In The Duodum 12 - Radjabova Azizakhanum Farmonovna (Zien Journals, 2023)
The Duodenum Is Called The Central Link Of Digestion. The Acidic Gastric Chyme That Enters The Intestine Is Alkalized Under The Influence Of Digestive Juices, Which Creates An Optimal Environment For Further Hydrolysis Of Nutrients. Three Digestive Juices Are Secreted Into The Cavity Of The Duodenum: Pancreatic, Intestinal And Bile. Pancreatic Juice. The Exocrine Elements Of The Pancreas Secrete Pancreatic Juice, Which Is Secreted Through The Ducts Into The Duodenal Cavity. 1.5–2.5 Liters Of Juice Is Formed Per Day. Pancreatic Juice Is A Colorless Transparent Liquid. Composition Of Pancreatic Juice: 99% - Water, 1% - Dry Residue. The Dry Residue Consists Of Inorganic And Organic Substances. Inorganic Substances Are Represented By Sodium, Potassium, Calcium, Magnesium Chlorides, Sulfates And Phosphates
Keywords: Duodenum; Trypsin; Chymotrypsin; Bile